O debate histórico-social nas discussões sobre o jogo Kingdom come: deliverance: identidades e medievalismos nos espaços virtuais no século XXI (2013-2018) - Meotti, Diego Neivor Perondi (2023)
The goal of this work is to analyze how identities were manifested in the digital space, between the years 2013 and 2018, around the electronic game Kingdom Come: Deliverance (2018). The game in question became the center of discussion for the fact that it was advertised as a game that would seek a historical accuracy. This proposal made a portion of the public question elements that could be absent in the game, such as ethnic groups, generating discussions of a social political nature about how the nationalist ideas of its main developer, Daniel Vávra, could be present in the game. We will focus on analyzing parts of the game that allow us to reflect on how different ethnic groups were represented in the game, and how these elements propagate ethnically-based nationalist ideas, based on Vávra's ideas, manifested not only in the game, but also in his interviews and presentations. In addition to the game and its developer, we seek to discuss the political and social identities of the audience manifested in online discussions. These manifestations differ from those of Vávra due to the reach of access made possible by the internet, in which its participants discussed themes from the past, but with interests mostly towards contemporaneity. For this research, we used the concept of identity, thinking about ethnic identity, and its effect when commercialized in a product focused on a global audience. In addition to this concept, we use the concept of medievalism, and neomedievalism, to understand how the medieval was enjoyed by the players in political discussions that took place in the blogs. Our hypothesis is that the game have strong elements of a nationalist identity also manifested in Vávra's speeches, and that the public, faced with his and other mediators' positions, discussed these themes in a way that, despite the debate about the past, focus on discussions in the present.